2014
DOI: 10.1097/mpg.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Inaccurate Weight Perception Is Associated With Extreme Weight‐Management Practices in US High School Students

Abstract: Objective To examine whether adolescents’ weight perception accuracy (WPA) was associated with extreme weight-management practices (EWPs) in differing body mass index (BMI) categories. Methods WPA, overassessment, and underassessment were determined by comparing self-reported BMI and weight perception among US high-school students in the 2009 National Youth Risk Behavior Survey. BMI was classified as: underweight (<5th percentile), healthy weight (5th–<85th), overweight (≥85th–<95th), and obese (≥95th). WPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 28 publications
2
45
1
Order By: Relevance
“…Initial database searches identified 10,398 unique records, and an additional 41 articles were identified by authors, from the reference lists of eligible articles or from supplementary searches. Full‐text review of 366 articles was completed, and 74 articles (indicated with asterisks in reference list) that described 78 studies were included in the review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial database searches identified 10,398 unique records, and an additional 41 articles were identified by authors, from the reference lists of eligible articles or from supplementary searches. Full‐text review of 366 articles was completed, and 74 articles (indicated with asterisks in reference list) that described 78 studies were included in the review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…There was moderate evidence for a relation between perceived overweight and unhealthy weight control strategies. The majority of cross‐sectional evidence suggested that perceived overweight was associated with higher likelihood of using unhealthy weight control strategies (12 findings from high‐quality studies and 13 from low‐quality studies ), but the strength of the evidence was downgraded to ‘moderate’ as an additional 10 findings were null , and 7 were mixed findings or suggested a negative relation (such that perceived overweight was associated with lower likelihood of using unhealthy weight control strategies) . There was strong evidence to suggest that perceived overweight was associated with greater use of unhealthy weight control strategies in the normal weight and no weight status criteria subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…Inaccurate perception of one's own body weight is a relatively common phenomenon observed in adolescents and adults [1][2][3][4][5][6][7][8]. It has been suggested that body weight misclassification may begin from adolescence and continue to adulthood [9][10][11], and that body weight misclassification may enhance vulnerability to some physical and mental health problems including increase in body weight, following unhealthy diet, anxiety, and depression [1,[12][13][14][15][16]. Arguably, the adolescent period is a particularly sensitive stage of life.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, extra weight and “plumpness” are noted as a sign of beauty, health, and affluence in certain cultures and ethnicities of the oil‐rich countries in the Arab region (Sibai et al, ; Wiesner & Ittel, ). Differentials may also be the consequence of different approaches in assessing weight perception, with some studies relying on a simple question about weight perception (Edwards et al, ; Hayward, Millar, Petersen, Swinburn, & Lewis, ; Ibrahim, El‐Kamary, Bailey, & St George, ; Zainuddin et al, ) and others showing “figure silhouettes” with a series of male and female body shapes of different sizes to report on adolescent's current body image (Al‐Sendi et al, ; Musaiger, bin Zaal, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the assessment of self‐perceived weight was based on a single question and may be prone to information bias. Yet the same questionnaire item has been used in other regional and international studies (Edwards et al, ; Hayward et al, ; Ibrahim et al, ; Zainuddin et al, ), providing us with the opportunity to compare our findings with those in the literature. Using a different instrument such as figure silhouettes in future studies would enhance the validity of the results.…”
Section: Discussionmentioning
confidence: 99%